Integrating Digital Technology and Human Values from the Perspective of Educational Philosophy - Mohammad Nurul Burhan; Ari Abi Aufa (CV. Agrapana Media, 2026)
The rapid integration of digital technology in education risks reducing the humanistic and ethical dimensions of learning by prioritizing efficiency, standardization, and data-driven outcomes over values such as empathy, dialogue, and character formation. This study aims to analyze the integration of digital technology and human values from the perspective of educational philosophy. This research employs a qualitative approach using library research methods. Philosophical analysis is conducted through ontological, epistemological, and axiological perspectives to understand the position of technology within education. The findings reveal that digital technology should be positioned as a pedagogical tool that supports the humanization process rather than as the ultimate goal of education. Educational philosophy plays a crucial role in providing ethical and humanistic direction so that the use of digital technology remains oriented toward the holistic development of learners, encompassing intellectual, moral, social, and spiritual dimensions. This study contributes to strengthening the philosophical foundation of technology integration in Islamic and general education.